Analisis Pemanfaatan Sumber Kekuasaan Pemimpin Sekolah SMA Islam Plus Hidayathut Thulab Semen Kediri - Hadi, Muhammad Abdul; Susilo, Suko (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
Leadership style is a behavioral norm used by a leader when he tries to influence the behavior of people or subordinates as they see it. This was also shown by the leader of SMA Islam Plus Hidayatut Thullab Semen Kediri who always carried out leadership behavior in carrying out his duties as school principal. The focus of this research discusses 1) The tendency to use sources of power in the leadership behavior of the Islamic Senior High School Plus Hidayatut Thullab Petuk Semen Kediri school principal. 2) Tendency of leadership behavior of the head of SMA Islam Plus Hidayatut Thullab Petuk Semen Kediri. Several aspects of this study used descriptive qualitative research, and in the process of collecting data the researchers used the methods of observation, documentation, and interviews. As for the analysis, the researcher used the Milles and Huberman technique. The results of the study 1) In the practice of leadership, the principal of SMA Islam Plus Hidayatut Thullab Petuk Semen Kediri turned out to be an Expert Power who tends to have a dominant influence on his subordinates. 2). The leadership behavior of the head of SMA Islam Plus Hidayatut Thullab Semen Kediri in carrying out his duties as a principal is leadership behavior that is oriented towards fostering group cohesiveness in carrying out a number of school activities at SMA Islam Plus Hidayatut Thullab Petuk Semen Kediri such as: compromizzing, gatekeeping and encouraging behavior